Economic evaluation of typhoid vaccination in a prolonged typhoid outbreak setting: The case of Kasese district in Uganda. Issue 17 (21st April 2015) - Carias, Cristina; Walters, Maroya Spalding; Wefula, Edward; Date, Kashmira A.; Swerdlow, David L.; Vijayaraghavan, Maya; Mintz, Eric
Abstract Background Vaccination has been increasingly promoted to help control epidemic and endemic typhoid fever in high-incidence areas. Despite growing recognition that typhoid incidence in some areas of sub-Saharan Africa is similar to high-incidence areas of Asia, no large-scale typhoid vaccination campaigns have been conducted there. We performed an economic evaluation of a hypothetical one-time, fixed-post typhoid vaccination campaign in Kasese, a rural district in Uganda where a large, multi-year outbreak of typhoid fever has been reported. Methods We used medical cost and epidemiological data retrieved on-site and campaign costs from previous fixed-post vaccination campaigns in Kasese to account for costs from a public sector health care delivery perspective. We calculated program costs and averted disability-adjusted life years (DALYs) and medical costs as a result of vaccination, to calculate the cost of the intervention per DALY and case averted. Results Over the 3 years of projected vaccine efficacy, a one-time vaccination campaign was estimated to avert 1768 (90%CI: 684–4431) typhoid fever cases per year and a total of 3868 (90%CI: 1353–9807) DALYs over the duration of the immunity conferred by the vaccine. The cost of the intervention per DALY averted was US$ 484 (90%CI: 18–1292) and per case averted US$ 341 (90%CI: 13–883). Conclusion We estimated the vaccination campaign in this setting to be highly cost-effective, according to WHO's cost-effective guidelines. Results may be applicable to other African settings with similar high disease incidence estimates.